Impact of Pandemic on Public Transportation Service in Kota Kinabalu - Lillian Gungat; Dayang Russalnie Deh; Mohd. Azizul Ladin; Jodin Makinda; Elsa Eka Putri (UniSE Press, 2022)
Implementation of the Movement Control Order during pandemic with new regulations is expected to have consequential destruction to all service sectors and increase the disruption risk factor for future public transportation planning. Hence, it is necessary to investigate the people's travel behaviors and perceptions related to pandemic and public transportation service as part of the impact assessment for sustainability of public transportation operation. This study was conducted in the city of Kota Kinabalu, Sabah where questionnaire surveys were distributed to respondents and results were analyzed using statistical analysis methods. The McNemar Bowker and Wilcoxon Signed-Rank tests proved that there are significant impacts of COVID-19 pandemic to the mobility characteristics and travel mode preference on using public transport for primary outdoor trips. The number of trips completed were significantly reduced, while the choices of transport mode were also influenced by the spread of COVID-19 whereby respondents choosing to avoid public transportation. The findings also showed differences in travel behaviors concerning demographic factors. Based on the respondent perception on pandemic COVID-19, 71% agree that probability of being infected is higher when using public transport. Hence, public transport sector needs to strictly follow the standard operating procedure during pandemic to attract more public transport usage for economic sustainability.